2010
DOI: 10.1175/2010bams2770.1
|View full text |Cite
|
Sign up to set email alerts
|

Whither the Stable Boundary Layer?

Abstract: C learly no other part of the atmosphere is more important to Earth's ecosystems than its lowest layer, known as the atmospheric boundary layer (ABL). The land surface exchanges heat, mass, and momentum with the free atmosphere through the ABL, and naturally the ABL is affected by orography, land use, external forcing (e.g., radiation), and Earth's rotation. Environmental changes, whether due to slowly evolving global warming or rapidly dispersing atmospheric releases, permeate through to living organisms via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(55 citation statements)
references
References 44 publications
0
55
0
Order By: Relevance
“…To alleviate this shortcoming, many recent RSM were designed Ri cr -free [92][93][94][95][96]. This new development in modelling of stably stratified turbulent flows was highlighted in the recent overviews by Fernando & Weil [97] and McFarlane [98]. The absence of Ri cr is intrinsic to the QNSE theory while in RSM this feature needs to be introduced ad hoc in order to comply with data.…”
Section: (C) the Absence Of The Critical Richardson Numbermentioning
confidence: 99%
“…To alleviate this shortcoming, many recent RSM were designed Ri cr -free [92][93][94][95][96]. This new development in modelling of stably stratified turbulent flows was highlighted in the recent overviews by Fernando & Weil [97] and McFarlane [98]. The absence of Ri cr is intrinsic to the QNSE theory while in RSM this feature needs to be introduced ad hoc in order to comply with data.…”
Section: (C) the Absence Of The Critical Richardson Numbermentioning
confidence: 99%
“…Stated briefly, both observations and modelling results show that the criteria for atmospheric instability are strongly scale dependent, with the criteria being met much more often as scale size decreases. Thus, although the atmosphere may appear statically and dynamically stable when examined on vertical scales of a hundred metres or more, smaller-scale temperature and velocity gradients arising from a combination of pre-existing low-level, small-scale turbulence, linear or non-linear gravity waves, and similar factors can significantly enhance the unstable nature of the atmosphere at these smaller scales (see comments in Tjernström et al 2009, Fritts et al 2009, and Fernando and Weil 2010.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally acknowledged that non-neutral atmospheric stability conditions pose one of the greatest challenges for MMs (Fernando and Weil, 2010). To study the performance of the models in different stability regimes, the stability parameters supplied for each model (inverse Obukhov length or bulk Richardson number) were used to group the hourly samples into five stability classes based on Gryning et al (2007) and Mohan and Siddiqui (1998), shown in Table 2.…”
Section: Effect Of Atmospheric Stabilitymentioning
confidence: 99%